Exploration of Thematic, Diagnostic & Prognostic Frames: A Study on Military Operations in Pakistan - sadaf, ayesha; Ayesha Sadaf (Journal of Peace, Development and Communication, 2022)
Present study aims to explore news framing by English dailies of Pakistan regarding Military Operations being conducted across country. News stories were analyzed from 2001-2015. English dailies were taken from biggest conglomerates of Pakistan i.e, Daily Dawn, The News and The Nation. News stories selected via systematic probability sampling. Results indicate that there is a significant difference of thematic framing in news stories of English dailies related to Military Operations, as compared to diagnostic and prognostic framing. Findings also revealed that English dailies vigilantly reported news stories in identifying problems and giving solutions. Key words: Military Operations, Framing, English Dailies, Content Analysis, Diagnostic framing, thematic framing, prognostic framing, framing analysis.